Fiscal reality of the municipalities of the Santander Department in the framework of the process of the fiscal decentralization in Colombia, 2004-2012 - Asela Molina, Jorge Enrique (Universidad Pedagógica y Tecnológica de Colombia, 2015)
This document explores the decentralization process in Colombia through its normative framework and its relation with the public finances of the municipalities of Santander Department, by means of the analysis of fiscal situation of local authorities of the Department during 2004-2012. For this exercise have been taking as reference the indicators of intergovernmental dependence and fiscal effort, proposed by the National Department of Planning (DNP, by its Spanish acronym), showing in most of the cases problems in the generation of own resources and one high degree of dependence from the transfers of the central government.